2006
DOI: 10.1681/asn.2006020156
|View full text |Cite
|
Sign up to set email alerts
|

International Differences in Dialysis Mortality Reflect Background General Population Atherosclerotic Cardiovascular Mortality

Abstract: Existing national, racial, and ethnic differences in dialysis patient mortality rates largely are unexplained. This study aimed to test the hypothesis that mortality rates related to atherosclerotic cardiovascular disease (ASCVD) in dialysis populations (DP) and in the background general populations (GP) are correlated. In a cross-sectional, multinational study, all-cause and ASCVD mortality rates were compared between GP and DP using the most recent data from the World Health Organization mortality database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 34 publications
2
74
2
Order By: Relevance
“…The European and worldwide experience suggests that the frequency of cardiac death in the dialysis population varies in parallel with its frequency in the background population: 27% of the variation in the frequency of cardiac death in the dialysis population is explained by the mortality in the general population (16,17). This observation would suggest that the dialyzed patients largely die as the result of the same cardiovascular causes as individuals in the general population.…”
Section: Inspector Gregory) "Is There Anything You Wish To Draw My Atmentioning
confidence: 99%
“…The European and worldwide experience suggests that the frequency of cardiac death in the dialysis population varies in parallel with its frequency in the background population: 27% of the variation in the frequency of cardiac death in the dialysis population is explained by the mortality in the general population (16,17). This observation would suggest that the dialyzed patients largely die as the result of the same cardiovascular causes as individuals in the general population.…”
Section: Inspector Gregory) "Is There Anything You Wish To Draw My Atmentioning
confidence: 99%
“…Regional US data have shown that mortality for dialysis patients varies by region and correlates with mortality differences in the general population (8); therefore, one may hypothesize that higher mortality in US dialysis patients is partly explained by higher mortality in the general population. Using data from national ESRD registries and DOPPS, Yoshino et al (9) correlated national mortality rates among dialysis patients with national mortality data for the general population from the World Health Organization. A strong association was found, suggesting that countries with relatively high mortality rates in the general population also have relatively high mortality rates in the dialysis population.…”
Section: Regional Mortality Differences In the General Populationsmentioning
confidence: 99%
“…doi: 10.1681 Patients who have stage 5 chronic kidney disease (CKD) and are on dialysis therapy have a high mortality rate, estimated between 14 and 26% in Europe and at 24% per year in the United States. 1 The accumulation of various retention solutes over a broad range of molecular weights and chemical composition is involved in the complex pathophysiology of uremia and, among other factors, implicated in the high mortality observed in CKD. 2 Because of their higher porosity, high-flux hemodialysis (HD) membranes have the capacity to remove retention solutes of higher molecular weight than do low-flux membranes, 3 which contain smaller pores.…”
Section: Introductionmentioning
confidence: 99%